1994
DOI: 10.1007/bf02336773
|View full text |Cite
|
Sign up to set email alerts
|

Insertional mutagenesis in transgenic mice

Abstract: Increasing numbers of transgenic mouse lines have resulted in several dozens of mutants created by insertional mutagenesis. The advantages of different vector systems and the problems associated with the analysis of mutations and the cloning of the affected genes are discussed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 85 publications
0
27
0
2
Order By: Relevance
“…A review of 35 different insertional mutants generated in transgenic mouse lines revealed that some chromosomes are selected more often for illegitimate integration than others, at least in this limited subset. 61 For example, 5/35…”
Section: Illegitimate Integration Sites Are Not Totally Randommentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 35 different insertional mutants generated in transgenic mouse lines revealed that some chromosomes are selected more often for illegitimate integration than others, at least in this limited subset. 61 For example, 5/35…”
Section: Illegitimate Integration Sites Are Not Totally Randommentioning
confidence: 99%
“…43,52,60 Another consequence is that the integrated material can interrupt coding sequences. 61 Indeed, an estimated 15% of all transgenic mouse lines studied had incurred mutations due to DNA integration. 50,51 This is a remarkably high rate of induced change, considering that only about 2-3% of the most extensively sequenced mammalian genome (that of homo sapiens) is made up of coding sequences, 62 whose disruption could give rise to a distinct phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…154) as well as the expression of the transgene itself may also be severely compromised by surrounding elements (variegation effects; Ref. 110). As a solution to this recurring problem single-copy integration of the transgene into a selected site or the use of so-called insulator elements has been described (14,23,36,41,97).…”
Section: Basic Constitutive Transgenic Strategiesmentioning
confidence: 99%
“…Randomly integrated transgenes can induce insertional mutations in endogenous genes, amplified by severe alterations of flanking chromosomal regions. Although several thousand transgenic lines have been published, the number of reported insertional mutants is very low so far (reviewed by Rijkers et al 1994). Taking into account that only viable and fertile mutants causing strong phenotypes were identified in characterized lines, the real frequency of insertional mutations should clearly be higher.…”
Section: Position Effects On Transgene Expressionmentioning
confidence: 99%